From Cockle Shell to Bioceramic Root Canal Sealer: The Manufacturing and its Physical and Biological Properties - Chanathip Chatphatthanasiri; Thanakorn Wasanapiarnpong; Theerapat Chanamuangkon; Pavena Chivatxaranukul; Pairoj Linsuwanont (International Dental Journal, 2025)
Introduction and aims: Cockle shells, which are discarded as waste by the food industry, have been used in medical fields. This study aimed to manufacture a newly developed cockle shell-derived bioceramic sealer (NDBS) and evaluate its physical and biological properties. Methods: Cockle shell-derived tricalcium silicate (C-C3S) was synthesized via the solid-state reaction technique and analysed for chemical composition and particle size. NDBS was prepared by mixing C-C3S with specific additives. The chemical composition and surface morphology of fully set sealers were assessed using X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy. Physical properties were tested according to International Organization for Standardization 6876 standards. For biological testing, both sealers were extracted and diluted for cytotoxicity and proliferation assays on human periodontal ligament cells using the MTT assay. Reverse transcription-quantitative polymerase chain reaction was performed to evaluate changes in proinflammatory (interleukin-6, interleukin-8, tumour necrosis factor-alpha-α) and mineralization (alkaline phosphatase) gene expression. Results: C-C3S was found to contain 55% tricalcium silicate with a particle size of 5.32 microns. Both fully set sealers contained tricalcium silicate and calcium silicate hydrate. They demonstrated acceptable flowability, setting time, film thickness, and radiopacity, although their solubility exceeded International Organization for Standardization limits. Both sealers maintained a pH above 7, with no significant difference in calcium release after 2 weeks. The MTT assay indicated improved cell viability with increasing dilution. Reverse transcription-quantitative polymerase chain reaction showed that both sealers showed a tendency to reduce proinflammatory gene expression. Both sealers showed a tendency to upregulate alkaline phosphatase gene expression. Conclusion: Within the limitations of this study, it was shown that cockle shells can be used to manufacture NDBS, which demonstrated physical and biological properties comparable to those of iRoot SP. Clinical relevance: This study highlights the potential of NDBS to be further developed as a root canal sealer.